The Influence of Leadership, Motivation, and Work Environment on Employee Performance Through Job Satisfaction as a Mediating Variable - Nurbaeti, Nurbaeti; Badawy Saluy, Ahmad; Bari, Abdul (Green Publisher, 2023)
This study aims to analyze the factors that influence employee performance, including: leadership, work motivation, work environment and job satisfaction. This study also wants to analyze the influence of leadership, work motivation, and organizational culture on job satisfaction and analyze how job satisfaction mediates the influence of leadership, work motivation and work environment on employee performance. The population in this study amounted to 130 permanent employees at PT TI. The sample used was 99 employees using the Slovin formula calculation. The sampling technique used was simple random sampling technique which was carried out randomly without regard to strata in the population. The research method used is quantitative with SEM-PLS. Based on the analysis in this study, the results show that: 1) Leadership has no significant effect on job satisfaction; 2) Work motivation has a positive and significant effect on job satisfaction; 3) The work environment has no significant effect on job satisfaction; 4) Leadership has no significant effect on employee performance; 5) Work motivation has no significant effect on employee performance; 6) The work environment has a positive and significant effect on employee performance; 7) Job satisfaction has a positive and significant effect on employee performance; 8) Job satisfaction does not mediate the influence of leadership on employee performance; 9) Job satisfaction mediates the effect of work motivation on employee performance; 10) Job satisfaction does not mediate the influence of the work environment on employee performance.